HUBUNGAN ANTARA KEGIATAN ANAK PADA BERMAIN PERAN MIKRO DENGAN KETERAMPILAN BERBICARA ANAK USIA DINI - Nuranita Oktavia (Al-Abyadh, 2023)
One way to improve children's speaking skills is through the use of activities known as micro role playing. A quantitative research approach was taken in this study. This study uses a correlational approach to examine the relationship between children's activities in micro role playing (X) and early childhood speech skills (Y). Finding a link between the two is the focus of this research. The strength of this relationship can be measured by the correlation coefficient, and its statistical significance can be determined by looking at the numbers. The research results show that; first, children's activities in micro role playing in group B RA Al-Wafi Bandung obtained an average value of 86. This value is in the interval 80-100 with a very good interpretation. This means that the children's activities in micro role playing in group B RA Al-Wafi Bandung have very good qualifications. Second, the speaking skills of early childhood in group B RA Al-Wafi Bandung obtained an average value of 76. This number may be reasonably interpreted as being within the range of 70–79. This indicates that the proficiency levels of group B RA Al-Wafi Bandung's preschoolers in the use of the English language are high. Third, in group B at RA Al-Wafi Bandung, there is a reasonably strong to moderate association between children's involvement in micro role acting and their early childhood speaking abilities